Young People Leisure Activities Transformation during Quarantine Self-Isolation: Characteristics and Regulation Problem - Mischenko, Elena V.; Fabrikov, Maxim S.; Martynenko, Elena V.; Martynenko, Stanislav E.; Smirnov, Viktor M.; Ibraeva, Gulnara R.; Kosenko, Andrey V. (Cuestiones Políticas, 2020)
The objective of the research is to study the characteristics of leisure activities of young people in self-isolated conditions during the coronavirus pandemic. As a research method, the authors use an online survey that allowed them to more effectively visualize the features of leisure activities and the peculiarities of their regulation among self-isolated students. The article also considers the leisure strategies of young people in conditions of self-isolation and social fortune. The novelty of the research lies in the fact that the hierarchy of leisure preferences of young people was studied for the first time during the period of self-isolation. It is concluded that the leisure practices of young people are identified by the regular use of the Internet, instead of the use of sports or any other practice. The priority areas of the Internet application are: study and communication, reading books and consulting news. In addition, there is the ability to communicate on social networks, search for video and audio recordings and games on the network. Preferred game genres are shown to be multiplatform simulators and strategies.